1961
DOI: 10.1002/aic.690070334
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous phase and volumetric behavior of the methane n‐heptane system at low temperatures

Abstract: A, reactor, sq.cm. a unit of volume, cm.-l C = concentration, moles/liter D = molecular diffusivity, sq.cm./ f = fractional acid conversion, dik = first-order reaction velocity L = bed height n = number of spheres MI = cross-sectional area of empty = packed bed surface area per sec. mensionless constant = mass flux rate for a single reacting sphere, moles/sq.cm-superficial velocity, dimensionless = molar concentration of surface active sites = over-all rate of reaction, moles/liter sec. = interfacial condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1962
1962
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 13 publications
2
27
0
Order By: Relevance
“…A quadruple point has been reported by Chang et al [13] and Kohn [14] for the methane-n-heptane system and by Chang and Kobayashi [15] for the methane-toluene system. For such systems, the solubility curve is not continuous from low temperatures up to the solute melting point.…”
Section: Resultsmentioning
confidence: 81%
“…A quadruple point has been reported by Chang et al [13] and Kohn [14] for the methane-n-heptane system and by Chang and Kobayashi [15] for the methane-toluene system. For such systems, the solubility curve is not continuous from low temperatures up to the solute melting point.…”
Section: Resultsmentioning
confidence: 81%
“…(6) The three-phase curve {solid heptane (s C7 ) + liquid + vapour} interrupts the three-phase curve l 2 l 1 g at a quadruple point s C7 l 2 l 1 g. (6) Mixtures incorporating an n-alkane with carbon number n e 8 do not show stable (liquid+liquid) equilibria. In these mixtures the three-phase curve (solid high n-alkane+liquid+vapour) (s Cn lg) consists of two branches, as can be seen in figure 1.…”
Section: Introductionmentioning
confidence: 98%
“…At cryogenic temperatures and high pressures, systems such as methane, nheptane (Kohn, 1961) and nitrogen, propane (Schindler et al, 1966) have been reported to show liquid miscibility gaps.…”
Section: Scopementioning
confidence: 97%